In silico identification of molecular mimicry between T-cell epitopes of borrelia burgdorferi and the human proteome: implications for autoimmune response in Lyme disease - Tanim, Tahsin Mahmud (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2022.